2016
DOI: 10.1016/j.cell.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Stress Induces Chromatin Reorganization to Promote Longevity and UPR mt

Abstract: Summary Organisms respond to mitochondrial stress through the upregulation of an array of protective genes, often perpetuating an early response to metabolic dysfunction across a lifetime. We find that mitochondrial stress causes widespread changes in chromatin structure through histone H3K9 di-methylation marks traditionally associated with gene silencing. Mitochondrial stress response activation requires the di-methylation of histone H3K9 through the activity of the histone methyltransferase met-2 and the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
333
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(342 citation statements)
references
References 43 publications
8
333
0
1
Order By: Relevance
“…Analogous findings were also observed with the mammalian homologs of JMJD-1.2 (Phf8) and JMJD-3.1 (Jmjd3), suggesting a conserved mechanism of UPR mt regulation (23). In the second study, the H3K9 methyltransferase MET-2 and the novel protein LIN-65 were found to positively regulate the UPR mt (24). LIN-65 is initially cytosolic but localizes to the nucleus in the presence of mitochondrial stress in a MET-2-dependent manner (24), suggesting they are functionally A, in C. elegans, the UPR mt is principally regulated by the bZIP transcription factor ATFS-1 that contains both mitochondrial and nuclear sorting sequences.…”
Section: Caenorhabditis Eleganssupporting
confidence: 61%
See 1 more Smart Citation
“…Analogous findings were also observed with the mammalian homologs of JMJD-1.2 (Phf8) and JMJD-3.1 (Jmjd3), suggesting a conserved mechanism of UPR mt regulation (23). In the second study, the H3K9 methyltransferase MET-2 and the novel protein LIN-65 were found to positively regulate the UPR mt (24). LIN-65 is initially cytosolic but localizes to the nucleus in the presence of mitochondrial stress in a MET-2-dependent manner (24), suggesting they are functionally A, in C. elegans, the UPR mt is principally regulated by the bZIP transcription factor ATFS-1 that contains both mitochondrial and nuclear sorting sequences.…”
Section: Caenorhabditis Eleganssupporting
confidence: 61%
“…Indeed, both MET-2 and LIN-65 are required for the methylation of histone H3K9 that is needed for accumulation of the UPR mt transcriptional regulator DVE-1 into discrete nuclear puncta, specifically to chromatin regions thought to represent sites of active gene expression (9,24). These findings add an extra layer of complexity to the regulation of the UPR mt , suggesting that epigenetic modifications are a necessary step for the activation of this mitochondrial recovery program.…”
Section: Caenorhabditis Elegansmentioning
confidence: 92%
“…A novel study reports the role of mitochondria in cytosolic protein homeostasis, wherein aggregated cytoplasmic proteins are imported into the mitochondria for degradation [68]. There are several reports that mitochondria can epigenetically regulate the nucleus both at the level of DNA and histones [69,70]. While the exact cellular mechanism is not yet elucidated, the upregulation of TET proteins-the only known effectors of hydroxymethylation of cytosines in nuclear DNA-and the resulting epigenetic changes in the nuclear gene signature is documented under conditions of oxidative stress [71].…”
Section: Mitochondrial Targeted Therapy In Allergy Asthma and Metabomentioning
confidence: 99%
“…The UPR mt is a nascent cellular pathway that is activated when cells experience mitochondrial protein folding stress and retrograde signaling from the mitochondria to the nucleus triggers transcriptional activation of nuclear‐encoded mitochondrial chaperones and proteases as well as repression of translation to reestablish proteostasis (Haynes, Fiorese & Lin, 2013; Haynes & Ron, 2010; Mohrin et al., 2015; Munch & Harper, 2016; Zhao et al., 2002). Primarily characterized in C. elegans , the UPR mt is activated during a developmental stage when there is a burst of mitochondrial biogenesis (Houtkooper et al., 2013; Lin et al., 2016; Merkwirth et al., 2016; Nargund, Pellegrino, Fiorese, Baker & Haynes, 2012; Pellegrino et al., 2014; Tian et al., 2016). It is therefore speculated that in stem cells, the UPR mt is activated under a physiological condition when mitochondrial biogenesis is induced.…”
Section: Introductionmentioning
confidence: 99%